O insólito no espaço-corpo do Cavaleiro inexistente e do Visconde partido ao meio, de ítalo Calvino - Rocha, Helen Cristine Alves (2016)
Taking the fact that the fantastic literature queries reality by means of tension between fantasy and the prosaic reality and that the literary space is multiple in meanings, what allows it to denunciate current ideologies in society, this dissertation aims at analyzing the way fantasy is treated and they way it can be understood in the body of two main characters by Italo Calvino, the Viscount and the Knight, from the books The nonexistent knight and The cloven viscount. So we intend to investigate from which representations fantasy emerges; how its manifestation is informed in the body-space of those main characters; which effects are followed in the narrative context; what other images are formed from them, taking into account both the Viscount’s and the Knight’s bodies are the space where fantasy emerges and inhabits. To achieve this goal, we study books where the specificity of fantastic literature is treated as theoretical fundament, mainly Calvino’s and the books which help understand it: José Paulo Paes (1985), Tzvetan Todorov (2004), Filipe Furtado (1980, 2015), David Roas (2001), Lenira Marques Covizzi (1978). For the psychoanalytic studies, we choose Freud (2010). On literary theory and literary history, we read Italo Calvino (1990, 1993, 1999, 2004, 2006). On language studies, ideology and space, we use Michel de Certeau (1998), Michel Foucault (2000, 2002, 2006), Marisa Martins Gama Khalil (2012, 2013), Gilles Deleuze and Félix Guattari (1995, 1997). Besides, we make a bibliographic research for situating Italo Calvino in his historical, social and cultural time as well as other critical studies about such themes and, this way, we envisage all the possible theoretical material for leading us to achieve our goals.